Rotation Elastogram Estimation Using Mechanical Assisted Spatial Compounding: A Simulation Study - Galaz-Donoso, B (Institute of Electrical and Electronics Engineers Inc., 2021)
In quasi-static ultrasound elastography the breast tumor classification may be done by using the rotation fill-in signature presents in the rotation elastogram, which is a marker of benignity that originate from the lesion rotation as a product of a laterally asymmetric stress field. However, the well-known low lateral resolution limitation of ultrasound imaging reduces the image quality of rotation elastogram. Studies using beam-steering, synthetic transmit aperture (STA) and diverging beam with STA methods have shown that the rotation elastogram quality can be significantly improved. In this context, we aim to study the feasibility of improve the rotation elastogram by mechanical assisted spatial compounding of displacements images from different ultrasound probe angles. We present a numerical study of the rotation elastogram contrast-to-noise enhancement by spatial compounding of displacement images obtained from quasi-static small compression at different ultrasound probe angles. Instead of steer electronically the insonofication beam, the ultrasound probe is rotated itself. Our results show that the contrast-to-noise ratio of the rotation elastogram can be significantly improved by increasing the number of displacement images used in the spatial compounding for small scanning angles. © 2021 IEEE.